Biochemical Assessment of Renal and Liver Function among Preeclamptics in Lagos Metropolis - Ekun, Oloruntoba Ayodele; Olawumi, Oluwatumininu Mary; Makwe, Christian Chigozie; Ogidi, Nkeiruka Ogochukwu (International Journal of Reproductive Medicine, 2018)
Objectives. Preeclampsia is a pregnancy specific syndrome. Studies have shown that preeclampsia has multiorgan dysfunction effects. This study evaluated biomarkers of renal and liver function among preeclamptic Nigerian women. Study Design. This was a cross-sectional study conducted among 49 preeclamptic women and 50 normotensive healthy pregnant women. Method. The baseline data comprising age, gestational age, and blood pressure were obtained. Venous blood and spot urine samples were collected from each participant. Plasma obtained from blood samples taken into lithium heparinized vacutainer bottles was assayed for electrolytes, urea, creatinine, total protein, albumin, and uric acid, while sera samples from blood samples taken into serum separation tube- (SST-) gel vacutainer were assayed for aspartate transaminase and alanine transaminase using ion selective electrode technique and Cobas autoanalyzer. Spot urine samples were assayed for protein and creatinine using Pyrogallol’s reagent and Jaffe’s methods, respectively. Microalbuminuria (protein/creatinine ratio) was generated from spot urine protein and creatinine data. Result. The plasma sodium, total protein, and albumin in preeclamptic group were significantly decreased (p<0.05) when compared with control. There was statistically significant increase (p<0.05) in microalbuminuria, plasma potassium, urea, creatinine, uric acid levels, serum AST, and ALT activities in preeclamptic group. A positive association (p<0.05) between alanine aminotransferase and biomarkers of renal function was observed. Conclusion. Preeclampsia has deleterious effects on renal and liver function as shown by alteration of these parameters.